Management challenges arising from a traumatic 360 degree cyclodialysis cleft - Amerasinghe N (Dove Medical Press, 2012)
S Trikha1, AMJ Turnbull2, SS Agrawal1, N Amerasinghe1, JF Kirwan11Department of Ophthalmology, Queen Alexandra Hospital, Portsmouth, 2Department of Ophthalmology, Royal Bournemouth Hospital, Bournemouth, UKAbstract: We describe the case of a 28-year-old naval officer who attended the ophthalmology service following blunt ocular trauma to the left eye. Clinical examination revealed a shallow anterior chamber, hypotony, and a 360° cyclodialysis cleft. We discuss the management options in this case, with an overview of the current literature.Keywords: cyclodialysis, cleft, hypotony, cryotherapy, trauma